Design of Competition Website Database at the University Level Using the Rapid Application Development (RAD) Method - Nur Anisa; Muhammad Wildan (Jurnal Indonesia Sosial Teknologi, 2024)
The development of the digital era has created high interest among students in taking part in competitions organized by universities to improve their practical skills. The Business and System Innovation Challenge (BASIC) an international competition which is held annually by the Faculty of Information Systems, a University in Jakarta, plays a role in facilitating this. However, the entire competition process is still carried out manually, which often makes teams experience difficulties in managing data. This problem can be overcome by designing a BASIC website database using the Rapid Application Development (RAD) method. The benefit of creating this system is that it makes it easier for participants to register for competitions and admins to manage data. Problem analysis was carried out by building entity relationship diagrams, the PHP programming language using the Laravel framework, and the MySQL database. The results of designing the BASIC website are features such as registering for competitions, uploading competition work results, providing feedback, and evaluating work results. Admin can also process data on the number of competition participants each year into a report. Data processing becomes faster and more accurate through complex database design.